2[(enH)2O2C-SO3].SnPhCl3 AND Cy2NH2O2C-SO3H.SnPhCl3.H2O: SYNTHESIS AND INFRARED STUDY - DAOUDA NDOYE; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
By allowing (enH)2O2C-SO3 (in water) and Cy2NH2O2C-SO3 (in ethanol) to react respectively with SnPh3Cl (in water) and SnPh2Cl2 (in ethanol) in specific ratios, the studied complexes are obtained. The suggested structures are discrete and tetrameric, the environment of the tin center being octahedral, the O2C-SO3H- anions behaving as a monodentate or a monochelating ligand.